La reestructuración cognitiva como estrategia para reducir niveles de depresión en mujeres víctimas de violencia intrafamiliar de entre 18 y 50 años usuarias del centro de equidad y justicia de Tumbaco en los meses de junio a septiembre de 2015 - Pozo Pozo, Diana Verónica (2016)
In this study, made as a requirement prior to obtaining the title of psychologist, the principal objective which is proposed is to reduce levels of depression identified in women, aged between 18 and 50, who are victims of family violence and who are users of the “Centro de Equidad y Justicia de Tumbaco”. Cognitive restructuring is the chosen strategy for intervention, based on the theoretical, cognitive behavioral approach of Aaron Beck and the rational, emotive therapy of Albert Ellis. This form of work also modifies those thoughts known as automatic or dysfunctional thoughts. The intervention was directed to a group of four patients for whom, by using the BDI-II test of Aaron Beck (1996), it was possible to identify levels of depression, ranging from mild to severe. The therapy was applied and there was a significant improvement. One conclusion is that a longer treatment time of psychotherapy could probably completely eliminate these occurrences of depression.